Ionic liquid confined spaces controlled catalytic CO2 cycloaddition of epoxides in BMIm.ZnCl3 and its supported ionic liquid phases. (March 2023) - Tomazett, Vinicius K.; Chacon, Gustavo; Marin, Graciane; Castegnaro, Marcus V.; das Chagas, Rafael P.; Lião, Luciano M.; Dupont, Jairton; Qadir, Muhammad I.
Abstract: Chemical fixation of CO2 to epoxides is an atom-economic and environment-benign approach to generate cyclic carbonates. Herein, we report efficient activation of the different aromatic and aliphatic epoxides at ambient reaction conditions. Our n-butyl-3-methylimidazulim trichlorozincate (BMIm.ZnCl3 ) ionic liquid presents higher activity with 56–95% conversion for the different aromatic and aliphatic epoxides from atmospheric pressure to 5 bar pressure at 40 °C. Small sized epoxides showed higher conversion and selectivity to cyclic carbonate as compared to bulky ones suggesting that the large epoxide substrates restricted diffusion into the confined spaces of BMIm.ZnCl3 IL, which limited the access of reactants to the catalytic active sites. By supporting the IL on the simple commercial SiO2, the confined SILP-ZnCl3 catalyst boosted the activity with maximum conversion and yield (99%) to cyclic carbonates under 10 bar at 100 °C. This higher performance could be attributed to the formation of the IL-cages onto SiO2 that enhances the local charge density and modulates the orientation of the IL near the surface to assist substantial charge transfer, leading to surface polarization and specific adsorption to ions. The reaction exemplifies a rare mechanism, supplemented by ex-situ ESI-MS analysis, in which epoxide 'O' is strongly H-bonded to the C2-H of imidazolium cation, while the ZnCl3 anion acts as nucleophile to facilitate the ring opening without its dissociation in chloride anion and ZnCl2, contrasting to the previous reports. Graphical Abstract: ga1 Highlights: Simple 1-n-butyl-3-methylimidazulim trichlorozincate (BMIm.ZnCl3 ) ionic liquid displays higher activity with 56–95% conversion for the different aromatic and aliphatic epoxides at 40 °C. Confined supported ionic liquid phase (SILP-ZnCl3 ) catalyst is represented remarkable TONs. Small sized epoxides demonstrate higher activity as compared to bulky ones due to their higher diffusion into the confined spaces of the IL with maximum access to the active sites. ESI-MS confirmed that the imidazolium cation of BMIm.ZnCl3 IL acted as Lewis acid and its anion, ZnCl3 anion, acts as nucleophile.